Lung Ultrasonography for the Diagnosis of Pleural Effusion in Children - Ayuningtyas, Dewi Sitoresmi; Martuti, Sri; Riza, Muhammad (Journal of Maternal and Child Health, 2021)
Background:Chest radiograph was currently the standard imaging for diagnosing pleural effusion. However, there were many limitations, namely radiation, varying interpretation, and long time to get results. Lung ultrasonography is an alternative procedure that is easy to learn and offers many benefits, including noninvasive, ra